Helpful local surtaxes? Florida and disadvantaged families. - Eger, III, Robert J.; McDonald, III, Bruce D.; Miller, D. Ryan (Local Government Studies, 2017)
Well-intended tax policy often produces unintended consequences. In this article, we look at one such tax policy, specialised surtaxes in the State of Florida. Surtaxes are frequently adopted to provide financial assistance to poverty-based local programmes and services. Despite the intended benefits, we show that the contributors of the tax have been able to capitalise the cost into the residential property market, ultimately placing the burden of the surtax upon the population its revenue intends to help.